EFEKTIVITAS WAKTU PENGAMBILAN DAN PENGUKURAN CONTOH GAS RUMAH KACA PADA PENGELOLAAN AIR DI LAHAN SAWAH - Anggri Hervani; A. Wiharjaka (Pusbindiklat - LIPI, 2014)
The agricultural sector is one of the greenhouse gases (GHG) sources and sinks. Inventory of GHG emis sionsintheagriculturalsectorisdonebyapplyingtheprincipleof measurable,reportable,verifiableorMRV, thusGHGmeasurement resultsarenotbiasedorunder/overestimate, reliable,andcheaper.The researchaimedto assess the most effective retrieval sampling time and measurement of greenhouse gas at different water manage mentsinricefield.Thefirstfactortreatmentwasthemanagementofirrigationwaterintheformsofcontinuous andintermittentirrigationusingarandomizedblockdesignwhichwasreplicatedthreetimes.Thesecondfactor treatmentwasthegassamplingtimeat6–7,9–10,12–13,15–16,and18–19.ObserveddatawasCO andCH fluxes.TheresultsshowedthatintermittentirrigationcouldreduceCH emissionsmorethan27%comparedto continuousirrigation.BasedonPearsoncorrelationvalue,samplingtimeandmeasurementofCO andCH were the most effective at 15–16 with correlation values of 0.901 and 0.984, respectively.